Modulating effect of emotional arousal intensity on selective attention in schizophrenia - Yu, Miaomiao; Dong, Bo; Qian, Feilong; Liu, Jingfang; Wu, Xiaogang (Frontiers in Psychiatry, 2025)
IntroductionThe interaction between attention and emotion is one of the key questions in schizophrenia, but the mechanisms of how emotional information affects selective attention in schizophrenia are still unclear.MethodsThe present study employed a cue-back-to-fixation procedure to manipulate the valence and emotional arousal intensity of stimuli presented at either cued locations (Experiment 1) or target locations (Experiment 2). The present study examined the impact of emotional arousal intensity on the inhibition of return (IOR)—a phenomenon characterized by faster responses to previously unattended relative to attended locations—in individuals with schizophrenia, during two distinct attentional phases: attentional disengagement and attentional reorientation.ResultsThe results showed significant IOR effects for both schizophrenia (Experiment 1a and 2a) and control groups (Experiment 1b and 2b) regardless of the emotional stimuli with different arousal intensities presented at both the cued and target locations. However, as compared with negative low arousal stimuli or neutral low arousal stimuli, significantly larger IOR effect size for control groups was found when negative high arousal stimuli were presented in cued location and for schizophrenia groups was found when negative high arousal stimuli were presented in target location.DiscussionThese results may underly the mechanism of attentional deficit for schizophrenia towards different arousal intensities of emotional stimuli. During the attentional disengagement phase, schizophrenia patients are more likely to filtered out those high-arousal stimuli that endanger life while control group participants experience enhanced perceptual processing towards them; during the attentional reorientation phase, schizophrenia patients display “hyperfocusing” on those life-threatening high-arousal stimuli while the control group manifest an “attentional blindness” phenomenon to avoid these threatening stimuli. Meanwhile, we also interpreted our findings in light of an alternative theory of salience dysregulation.